Code blue: Acinetobacter baumannii, a nosocomial pathogen with a role in the oral cavity. (27th September 2014) - Richards, A.M.; Abu Kwaik, Y.; Lamont, R.J.
Summary Actinetobacter baumannii is an important nosocomial pathogen that can cause a wide range of serious conditions including pneumonia, meningitis, necrotizing fasciitis and sepsis. It is also a major cause of wound infections in military personnel injured during the conflicts in Afghanistan and Iraq, leading to its popular nickname of 'Iraqibacter'. Contributing to its success in clinical settings is resistance to environmental stresses such as desiccation and disinfectants. Moreover, in recent years there has been a dramatic increase in the number of A. baumannii strains with resistance to multiple antibiotic classes. Acinetobacter baumannii is an inhabitant of oral biofilms, which can act as a reservoir for pneumonia and chronic obstructive pulmonary disease. Subgingival colonization by A. baumannii increases the risk of refractory periodontitis. Pathogenesis of the organism involves adherence, biofilm formation and iron acquisition. In addition, A. baumannii can induce apoptotic cell death in epithelial cells and kill hyphal forms of Candida albicans. Virulence factors that have been identified include pili, the outer membrane protein OmpA, phospholipases and extracellular polysaccharide. Acinetobacter baumannii can sense blue light through a blue‐light sensing using flavin (BLUF) domain protein, BlsA. The resulting conformational change in BlsA leads to changes in gene expression, including virulence genes.